Ontario freshwater fishes demonstrate differing range‐boundary shifts in a warming climate. Issue 2 (6th September 2013) - Alofs, Karen M.; Jackson, Donald A.; Lester, Nigel P.; MacIsaac, Hugh
Abstract Aim Northerly shifts, related to recent climate warming, have been observed in the distributions of taxa in many ecosystems and ecological roles. However, significant variation occurs among species in the magnitude of these shifts. Few studies have investigated the effects of climate warming on the distributions of freshwater species. Location A total of 1527 lakes across Ontario, Canada. Methods We used contemporary and historical survey data to examine the relationships between species occurrences and climate and to measure the magnitude and direction of northern range‐boundary shifts in 13 warm and coolwater freshwater fishes. We also tested whether range‐boundary shifts differed between baitfishes and sportfishes. We then related differences in species range‐boundary shifts to species traits including those related to dispersal, reproduction and ecological niche breadth. Results Many fishes are now more likely to occur in lakes where climate was historically limiting. Sportfish northern range boundaries shifted northward significantly over nearly 30 years at a rate of approximately 12.9–17.5 km per decade depending on the measure used; in contrast, baitfish northern range boundaries often shifted southward. Also, species traits explained much of the variation in species range boundaries. Main conclusions The northern range boundaries of warm and coolwater sportfishes in Ontario lakes appear to be shifting northward as expected based on observed climate warming. These species are shifting at rates comparable with taxa in marine and terrestrial ecosystems around the globe. In contrast to expectations, the northern range boundaries of small‐bodied baitfishes appear to often contract southward. Differences in range shifts by sportfishes and baitfishes may be related to dispersal, particularly by anglers and/or their ecological roles. Understanding the range‐boundary shifts underway in Ontario lake communities will help predict future shifts by freshwater fishes.